SOSIALISASI PEMBENTUKAN PERATURAN DESA PARTISIPATIF BERDASARKAN PERMENDAGRI NOMOR 111 TAHUN 2014 DI DESA BOLOK, KABUPATEN KUPANG - Jenny Ermalinda; Hernimus Ratu Udju; Cyrilius Wilton Taran Lamataro; Amirullah; Mardiana Hasbullah; Putri Mega Silvia Pa; Adhe Ismail Ananda; Yonas Benu; Muh. Taqwin Tahir (Universitas Mataram, 2026)
The administration of village government requires a set of rules based on the authority of the village. These rules are not only established by the village collectively, but also by village leaders independently or through agreements between village leaders, while still taking into account the national legal framework and the dynamics of local community needs. In practice, there is still a lack of understanding among village officials regarding Permendagri No. 111 of 2014 concerning Technical Guidelines for Regulations in Villages. This condition is exacerbated by the lack of guidance and training from the local government, resulting in the village head and the Village Consultative Body (BPD) not having the optimal capacity to formulate participatory and high-quality village regulations. The community service activity was held in Bolok Village, West Kupang District, Kupang Regency, with the aim of strengthening the knowledge and abilities of officials in the formation of participatory regulations, with 41 participants. The activity method was designed to encourage the active participation of village officials and the community in the formation of village regulations through socialization and interactive discussions. In addition, technical training on the drafting of village regulations was conducted in accordance with the provisions of Permendagri 111 of 2014 to improve understanding and practical skills. The results of the activity were measured through feedback from the participants, which showed an increase in their understanding of the mechanism for drafting village regulations based on applicable legal norms. Participants understood the importance of community involvement in every stage of the formulation of village regulations. In addition, participants were able to independently identify problems and formulate local needs to be included in village regulations. This activity also strengthened the capacity of village officials and BPDs in applying participatory principles that comply with legal principles. Overall, the activity contributed to improving the quality of village regulation formulation to be more democratic and responsive to public interests.